Porous tantalum combined hydrogel integrated bionic bone cartilage scaffold as well as preparation and application thereof
By combining porous tantalum with chitosan hydrogel, a bionic osteocartilage scaffold with a bilayer structure is formed, which solves the problem of osteocartilage defect caused by osteoarthritis, and achieves synchronous regeneration of bone and cartilage, with good biosafety and osteointegration capabilities.
Patent Information
- Application Number
- CN202510115995.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art is difficult to effectively solve the problem of osteocartilage defect caused by osteoarthritis. Especially in young people, traditional joint replacement surgery has limitations and lacks effective materials that can promote osteocartilage regeneration.
A bionic osteocartilage scaffold that combines porous tantalum and chitosan hydrogel is used to closely combine through physical cross-locking to form a porous tantalum hydrogel biphasic scaffold similar to natural osteocartilage.
This scaffold can simulate the structural characteristics of natural osteocartilage, promote synchronous regeneration of bone and cartilage, has good biosafety and bone integration capabilities, and is simple and easy to prepare, green and safe.
Smart Images

Figure CN119909233A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical materials, and in particular relates to a porous tantalum-hydrogel integrated bionic bone cartilage scaffold and a preparation method and application thereof. Background Art
[0002] Due to the high incidence of osteoarthritis in today's society, osteochondral defects in adults have attracted widespread attention. Osteochondral defects are usually caused by repetitive trauma within the joint, which may change the structure or composition of the bone. Joint tissue has a complex structure composed of cartilage and subchondral bone, which is a typical multi-layered structure. Traumatic osteochondral defects can affect the health of cartilage and bone. If left untreated, these defects will lead to the development of osteoarthritis (OA), eroding the original osteochondral structure, and severe cases may require joint replacement surgery. The current younger age of osteoarthritis makes the use of joint replacements full of limitations. For young people, the best way to treat degenerative lesions of osteochondral is to use scaffold materials to promote the regeneration of affected tissue.
[0003] The cartilage component in the joint tissue needs to be compensated by a hydrated viscoelastic matrix with a relatively low compression modulus. Hydrogel can meet the mechanical requirements of this component. Polysaccharide hydrogel can also promote cell adhesion, proliferation and differentiation into osteoblasts, making it a promising scaffold material in bone tissue engineering. The bone component requires a rigid framework with a relatively high modulus. Porous tantalum has good biocompatibility and an elastic modulus close to that of human bones, which helps to reduce the stress shielding effect and thus improve the bonding strength between the implant and the bone tissue. Porous tantalum also has osteoinductivity and can promote the occurrence of osteogenic reactions. The pore structure provides abundant space for cell and tissue growth, further enhancing its potential as a scaffold material for bone tissue engineering.
[0004] An ideal osteochondral scaffold should provide a suitable microenvironment for natural cell growth and promote tissue regeneration, while respecting the multilayer structure of natural tissue. Therefore, multilayer integral scaffolds have been widely studied in osteochondral defect repair. Multilayer scaffolds can simulate the inherent tissue structure of natural articular cartilage, promote tissue regeneration at the joint interface while restoring its structure. Therefore, this application proposes a bionic scaffold that simulates the inherent structure of natural joints, integrates osteochondral tissue, and promotes the regeneration of osteochondral defects at the joint. Summary of the invention
[0005] In order to solve the problems of the prior art, the present invention proposes a porous tantalum combined with hydrogel integrated bionic osteochondral scaffold and its preparation and application, so as to integrate the osteochondral tissue and promote the regeneration of osteochondral defects in joints.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold, which is a double-layer structure, wherein the lower layer is porous tantalum and the upper layer is chitosan hydrogel;
[0008] The lower porous tantalum layer is a layer for promoting bone regeneration, and the upper chitosan hydrogel layer is a layer for promoting cartilage regeneration;
[0009] The pores of the porous tantalum are 100 μm-500 μm, and the pores of the chitosan hydrogel are 5 μm-50 μm.
[0010] The present invention also provides a method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold, which is made by a perfusion process, and the specific steps are as follows:
[0011] Step 1. chitosan CS is added into the mixed solution, stirred, and freeze-thawed to obtain a CS solution;
[0012] Step 2. Place the porous tantalum on the lower layer of the mold, pour the chitosan solution on the upper surface of the porous tantalum, and let it stand to eliminate bubbles;
[0013] Step 3. After the porous tantalum and chitosan solution are physically cross-linked in a constant temperature box, the solution is taken out and immersed in ultrapure water to remove impurities, thereby obtaining a porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold.
[0014] In step 1, the mixed solution contains 0-5% LiOH, 5%-15% KOH, and 8%-15% urea in terms of mass percentage;
[0015] The number of freeze-thaw cycles is 2 to 4 times. During the freeze-thaw process, the freezing temperature is -40℃ to -50℃, and each freezing time is 4h to 10h. The thawing temperature is 4℃ to 10℃, and each time is 10h to 24h.
[0016] In step 2, the CS solution was allowed to stand at 4°C for 8 to 12 hours to eliminate bubbles;
[0017] The pouring amount of chitosan solution is adjusted according to the actual required thickness of chitosan gel layer;
[0018] In step 3, the cross-linking temperature is 25°C to 50°C; the cross-linking time is 3h to 24h;
[0019] Soak in ultrapure water for 7 days, changing the solution every 6 to 12 hours; the impurities removed are residual alkali and urea.
[0020] The porous tantalum combined with hydrogel integrated bionic osteochondrium scaffold provided by the present invention is used to implant the scaffold material into the osteochondrium defect to promote osteochondrium regeneration.
[0021] Compared with the prior art, the beneficial technical effects of the present invention are:
[0022] The present invention combines a porous tantalum metal scaffold with a polysaccharide hydrogel scaffold for the first time, mimics the structure and characteristics of natural osteochondral tissue, and constructs a porous tantalum hydrogel biphasic scaffold. Among them, porous tantalum is used as an osteogenic layer in the present invention, which is a recognized bone repair material with structural characteristics similar to trabecular bone, good biosafety and bone integration ability. For the hydrogel of the cartilage layer, it has a physical structure similar to that of the extracellular matrix, and its components are natural polysaccharide polymer materials, which are green, renewable and degradable, and have good biosafety. The porous tantalum and the hydrogel are tightly combined in a physically cross-interlocking manner and will not fall off, and the thickness of the double layer can be directionally controlled according to actual needs. The preparation method of the present invention is simple and easy, and does not use external chemical cross-linking agents, adhesives, etc., which is more green and safe. The biphasic scaffold provided by the present invention has similar characteristics to osteochondrium and has the potential to guide the synchronous regeneration of bone and cartilage. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image (500X) of the pure chitosan hydrogel side of Example 1;
[0024] Figure 2 A three-dimensional structural reconstruction diagram of the porous tantalum stent used in Example 1;
[0025] Figure 3 This is a morphology diagram of the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold in Example 1;
[0026] Figure 4 The scanning electron microscope image (a) and EDS spectrum element distribution diagram (b) of the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold of Example 1;
[0027] Figure 5 The EDS spectrum (a) and element content (b) of the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold in Example 1;
[0028] Figure 6 This is a flow chart of the surgical procedure of implanting porous tantalum combined with hydrogel integrated bionic osteochondral scaffold into a rat knee joint defect in Example 1;
[0029] Figure 7 The actual pictures of the porous tantalum combined with hydrogel integrated bionic osteochondral scaffold implanted in rat knee joints after reconstruction 4 weeks (a) and 8 weeks (b) after surgery in Example 1;
[0030] Figure 8 Micro-CT images of the porous tantalum combined with hydrogel integrated bionic osteochondral scaffold implanted in rat knee joints after reconstruction 4 weeks (a) and 8 weeks (b) after surgery in Example 1.
[0031] Fig. 9The degradation rates of the chitosan hydrogel in the porous tantalum-hydrogel integrated bionic osteochondrocyte scaffold of Example 1 after incubation in a simulated body fluid containing a lysozyme environment for 4 and 10 weeks. DETAILED DESCRIPTION
[0032] The present invention provides a porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold, which has a double-layer structure, wherein the upper layer is a bone regeneration promoting layer, and the lower layer is a cartilage regeneration promoting layer, wherein the bone regeneration promoting layer is porous tantalum, and the cartilage regeneration promoting layer is chitosan hydrogel, the pores of the porous tantalum are 100 μm-500 μm, and the pores of the chitosan hydrogel are 5 μm-50 μm.
[0033] The porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold provided by the present invention is prepared by the following method:
[0034] Step 1. Chitosan CS is added to a mixed solution of LiOH 0-5%, KOH 5%-15%, and urea 8%-15% by mass, stirred, and then frozen and thawed 2-4 times. During the freeze-thaw process, the freezing temperature is -40°C to -50°C, and the freezing is continued for 4h to 10h after reaching the set temperature; the dissolving temperature is 4°C to 10°C, and the temperature is continued to be kept warm for 10h to 24h after reaching the set temperature to obtain a CS solution.
[0035] Step 2. Place the porous tantalum in the lower layer of the mold, pour the CS solution on the upper surface of the porous tantalum according to the actual required thickness of the chitosan gel layer, and then let it stand at 4°C for 8h to 12h to eliminate bubbles.
[0036] Step 3. Soak the porous tantalum and CS solution in physical ultrapure water at 25°C to 50°C in a constant temperature box for 7 days, replace the solution every 6h to 12h, remove residual alkali and urea, and obtain a porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold.
[0037] The porous tantalum combined with hydrogel integrated bionic osteochondrium scaffold provided by the present invention is implanted in the osteochondrium defect to promote osteochondrium regeneration.
[0038] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.
[0039] Embodiment 1:
[0040] (1) 5 g of chitosan CS was added to a solution of LiOH:KOH:urea:H2O (4 g:8 g:9 g:79 g) and stirred. The mixture was frozen at -50 °C for 6 h and then thawed at 4 °C for 12 h. The mixture was freeze-thawed twice to obtain a 5 wt.% CS solution.
[0041] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0042] (3) The samples were placed at 4°C for 12 h to eliminate bubbles, and then physically cross-linked in a 37°C incubator for 12 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the water changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
[0043] The bionic osteochondral scaffold prepared in this embodiment is used to repair joint osteochondral damage.
[0044] The morphologies of the chitosan hydrogel and porous tantalum scaffold prepared in this example are shown in Figure 1 and Figure 2 Both are porous structures, and there are obvious differences in their pore structures, which fits the characteristics of large bone cells and small cartilage cells. The overall morphology of the scaffold was observed under an optical microscope, such as Figure 3 As shown in the figure, the lower layer of the stent is porous tantalum, and the upper layer is chitosan hydrogel. The hydrogel has been infused into the pores at the interface with the porous tantalum material, and the two structures are tightly fused. The microstructure of the stent was observed under a scanning electron microscope, as shown in the figure. Figure 4 As shown in the scanning electron microscope image of (a), the hydrogel layer has a dense structure, and the porous tantalum has uniform pores. At the interface, it can be seen that the hydrogel and the porous tantalum are combined with each other. At the same time, it can be seen from the results in the figure that the pore size of the tantalum scaffold in this embodiment is greater than 100μm, and the pore size of the hydrogel scaffold is less than 50μm, which are more specifically fitted to the needs of bone and cartilage, respectively. Figure 4 From the ESD energy spectrum element distribution diagram (b), it can be seen that C, O, and N at the interface are evenly distributed in the entire interface area. Figure 5 The element content at the interface shows that the hydrogel has been infused into the pores of the interface in contact with the porous tantalum, forming a porous tantalum combined with hydrogel integrated bionic osteochondrocyte scaffold with a lower layer promoting bone regeneration and an upper layer promoting cartilage regeneration. The integrated bionic osteochondrocyte scaffold prepared in this example was used to repair osteochondrocyte injury in the joints, and an osteochondrocyte injury model was constructed in the rat knee joint. Figure 6 The figure shows the implantation process of the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold. Eight weeks after the operation, the cartilage surface of the bone joint was basically healed without obvious defects, such as Figure 7 Micro-CT results ( Figure 8 ) also showed that after 8 weeks, the cartilage layer of the scaffold had a shadow, representing the cartilage tissue, and the scaffold was closely attached to the surrounding tissue, indicating that the new tissue grew well. The scaffold had good biosafety and the ability to promote osteochondral regeneration. In addition, the hydrogel scaffold can be biodegraded in a simulated body fluid environment containing lysozyme; the degradation was less than 20% at 4 weeks, indicating that the structural stability can be guaranteed to play a mechanical support function, and then gradually degraded by more than 50% within 10 weeks (see Fig. 9 ).
[0045] Embodiment 2:
[0046] (1) 4 g chitosan CS was added to a solution of LiOH:KOH:urea:H2O (4 g:8 g:9 g:79 g) and stirred. The solution was frozen at -40 °C for 10 h and then thawed at 10 °C for 10 h. The mixture was freeze-thawed twice to obtain a 4 wt.% CS solution.
[0047] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0048] (3) The samples were placed at 4°C for 12 h to eliminate bubbles, and then physically cross-linked in a 37°C incubator for 12 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the water changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
[0049] Embodiment 3:
[0050] (1) 2 g of chitosan CS was added to a solution of LiOH:KOH:urea:H2O (4 g:8 g:9 g:79 g) and stirred. The mixture was frozen at -50 °C for 6 h and then thawed at 4 °C for 24 h. The mixture was freeze-thawed twice to obtain a 2 wt.% CS solution.
[0051] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0052] (3) The samples were placed at 4°C for 12 h to eliminate bubbles, and then physically cross-linked in a 37°C incubator for 12 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the water changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
[0053] Embodiment 4:
[0054] (1) 5 g of chitosan CS was added to a solution of LiOH:KOH:urea:H2O (5 g:5 g:15 g:80 g) and stirred. The mixture was frozen at -40 °C for 10 h and then thawed at 10 °C for 10 h. The mixture was freeze-thawed twice to obtain a 5 wt.% CS solution.
[0055] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0056] (3) The samples were placed at 4°C for 8 h to eliminate bubbles, and then physically cross-linked in a 37°C incubator for 12 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the water changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
[0057] Embodiment 5:
[0058] (1) 4 g chitosan CS was added to a solution of LiOH:KOH:urea:H2O (2 g:13 g:8 g:77 g) and stirred. The solution was frozen at -40 °C for 10 h and then thawed at 10 °C for 10 h. The mixture was freeze-thawed 4 times to obtain a 4 wt.% CS solution.
[0059] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0060] (3) The samples were placed at 4°C for 24 h to eliminate bubbles, and then physically cross-linked in a 37°C incubator for 12 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the liquid changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic osteochondral scaffold.
[0061] Embodiment 6:
[0062] (1) 4 g chitosan CS was added to a solution of LiOH:KOH:urea:H2O (4 g:8 g:9 g:79 g) and stirred. The solution was frozen at -40 °C for 10 h and then thawed at 10 °C for 10 h. The mixture was freeze-thawed twice to obtain a 4 wt.% CS solution.
[0063] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0064] (3) The samples were placed at 4°C for 12 h to eliminate bubbles, and then physically cross-linked in a 50°C incubator for 6 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the liquid changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
[0065] Embodiment 7:
[0066] (1) 4 g chitosan CS was added to a solution of LiOH:KOH:urea:H2O (4 g:8 g:9 g:79 g) and stirred. The mixture was frozen and thawed twice to obtain a 4 wt.% CS solution.
[0067] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0068] (3) The samples were placed at 4°C for 12 h to eliminate bubbles, and then physically cross-linked in a 25°C incubator for 24 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the liquid changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
[0069] Embodiment 8:
[0070] (1) 4 g of chitosan CS was added to a solution of LiOH:KOH:urea:H2O (4 g:8 g:9 g:79 g) and stirred. The mixture was frozen at -40 °C for 10 h and then thawed at 10 °C for 10 h. The mixture was freeze-thawed twice to obtain a 4 wt.% CS solution.
[0071] (2) The porous tantalum is placed in a mold, and then a layer of chitosan solution is poured on its upper surface (the thickness of the gel layer is adjusted according to the actual needs)
[0072] (3) The samples were placed at 4°C for 12 h to eliminate bubbles, and then physically cross-linked in a 50°C incubator for 3 h. The samples were taken out and immersed in ultrapure water to fully remove alkali and urea impurities (washed with water for 7 days, with the liquid changed every 6 to 12 h). After cross-linking into gel, the samples were removed from the membrane to prepare a porous tantalum-hydrogel integrated bionic bone cartilage scaffold.
Claims
1. A porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold, characterized in that: The scaffold has a double-layer structure, the upper layer is a layer for promoting bone regeneration, and the lower layer is a layer for promoting cartilage regeneration; The bone regeneration promoting layer is porous tantalum, and the cartilage regeneration promoting layer is chitosan hydrogel.
2. The porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 1, characterized in that: The pores of the porous tantalum are 100 μm-500 μm, and the pores of the chitosan hydrogel are 5 μm-50 μm.
3. The porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 1, characterized in that: The thickness of the chitosan hydrogel layer is adjusted as needed.
4. The method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to any one of claims 1 to 3, characterized in that: Made by infusion process, including the following steps: Step 1. chitosan CS is added into the mixed solution, stirred, and freeze-thawed to obtain a CS solution; Step 2. Place the porous tantalum on the lower layer of the mold, pour the CS solution on the upper surface of the porous tantalum, and let it stand to eliminate bubbles; Step 3. After the porous tantalum and CS solution are physically cross-linked in a constant temperature box, the solution is taken out and immersed in ultrapure water to remove impurities, thereby obtaining a porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold.
5. The method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 4, characterized in that: In step 1, the mixed solution contains 0-5% LiOH, 5%-15% KOH, and 8%-15% urea.
6. The method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 4, characterized in that: In step 1, the number of freeze-thaw cycles is 2 to 4 times; during the freeze-thaw process, the freezing temperature is -40°C to -50°C, and each freezing time is 4h to 10h; the thawing temperature is 4°C to 10°C, and each time is 10h to 24h.
7. The method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 4, characterized in that: In step 2, the pouring amount of CS solution is adjusted according to the actual required thickness of the chitosan gel layer; and the solution is allowed to stand at 4° C. for 8 to 12 hours to eliminate bubbles.
8. The method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 4, characterized in that: In step 3, the mixture is immersed in ultrapure water for 7 days, and the solution is changed every 6 to 12 hours; the impurities removed are residual alkali and urea.
9. The method for preparing the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to claim 4, characterized in that: In step 3, the cross-linking temperature is 25° C. to 50° C.; and the cross-linking time is 3 h to 24 h.
10. The use of the porous tantalum combined with hydrogel integrated bionic bone cartilage scaffold according to any one of claims 1 to 3, characterized in that: The scaffold material is implanted into the osteochondral defect to promote osteochondral regeneration.
Citation Information
Cited By
Customizable two-phase hydrogel stent as well as preparation method and application thereof
CN120754328A
Bionic magnesium alloy material for inducing bone-cartilage synchronous regeneration and preparation method thereof
CN121971695A
Bionic magnesium alloy material for inducing synchronous bone-cartilage regeneration and preparation method thereof
CN121971695B